The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.vph.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane induces neurovascular protection against a systemic inflammatory challenge via both Nrf2-dependent and independent pathways

Abstract: Sepsis is often characterized by an acute brain inflammation and dysfunction, which is associated with increased morbidity and mortality worldwide. Preventing cerebral leukocyte recruitment may provide the key to halt progression of systemic inflammation to the brain. Here we investigated the influence of the anti-inflammatory and anti-oxidant compound, sulforaphane (SFN) on lipopolysachharide (LPS)-induced cellular interactions in the brain. The inflammatory response elicited by LPS was blunted by SFN adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
(67 reference statements)
2
29
0
1
Order By: Relevance
“…Sulforaphane (SFN), a well-known NRF2 promoter/activator, is an organic isothiocyanate naturally found in cruciferous plants such as broccoli and cabbage. SFN has been shown to possess neuroprotective properties in vitro as well as in vivo by activating the NRF2-KEAP1 pathway and enhancing the corresponding protein synthesis [122,[131][132][133][134][135][136][137][138][139]. Several studies revealed that in addition to the activation of NRF2, SFN could independently inhibit NF-kB activity.…”
Section: Current Treatments Of Tbimentioning
confidence: 99%
“…Sulforaphane (SFN), a well-known NRF2 promoter/activator, is an organic isothiocyanate naturally found in cruciferous plants such as broccoli and cabbage. SFN has been shown to possess neuroprotective properties in vitro as well as in vivo by activating the NRF2-KEAP1 pathway and enhancing the corresponding protein synthesis [122,[131][132][133][134][135][136][137][138][139]. Several studies revealed that in addition to the activation of NRF2, SFN could independently inhibit NF-kB activity.…”
Section: Current Treatments Of Tbimentioning
confidence: 99%
“…3), indicating a profound inflammatory response, possibly through increased expression of endothelial adhesion molecules [6, 11, 21]. Thus, we provide an additional evidence for the role of Nrf2 and importantly, ABCB10, in protection of BBB endothelium against inflammation.…”
Section: Discussionmentioning
confidence: 66%
“…Along with other beneficial effects of SFN, such as anti-inflammation [88]. Multiple in vitro and in vivo studies have demonstrated the ability of SFN to prevent various brain diseases, including stroke, TBI, AD, PD, and ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its BBB permeability, SFN can reach effective concentration in the CNS. Considering its other beneficial effects, such as anti-inflammation [88], SFN is a promising dietary and medical agent for neuroprotection.…”
Section: Resultsmentioning
confidence: 99%